The Relationship Between Students' Creativeness and Commitment in Class VII Social Studies Subjects at SMPN 45 Watupajung Sikka - Sina, Hendrikus; Kholiq, Abdul; Arifin, Muhamad Taufik (Lembaga Riset Mutiara Akbar, 2023)
The purpose of this study was to determine the relationship between creativity and student learning commitment in social studies subjects in class VII SMPN 45 Watu Pajung Sikka. This research was conducted at SMPN 45 Watu Pajung Sikka. The population of this study amounted to 55 students. The research sample was 50 students. The instrument consists of a questionnaire. The validation of this research is using the Person Prodact Moment formula through the SPSS v. program. 23 for windows. Data analysis technique using quantitative descriptive correlation. After the data is distributed. The results of the research data analysis showed that the correlation coefficient value was 0.339, which was positive or in the same direction, then a correlation value of 0.000 was obtained, or the relationship between the two variables was significant at the 0.05 level. This can be seen from the number of correlation coefficients. This value is compared with the rtable at a significant level of 5% for N = 50, the number is 0.279 and it can be seen that rcount > rtable or 0.339 > 0.279, so that the null hypothesis (H0) is rejected and the hypothesis (H1) is accepted. This means that there is a positive and significant relationship between students' creativity and learning commitment in social studies subjects in class VII SMPN 45 Watu Pajung Sikka